The music of Star Trek: Profiles in style - Bond, Jeff (Los Angeles Lone eagle, 1999)
The Music of Star Trek is a critical and historical overview of music scored for Paramount's Star Trek franchise, from the original '60s series to the highly successful Star Trek movies and the new television show spin-offs. This comprises some of the finest and most memorable music ever written for television or film, and has become a part of our American cultural heritage. The book features in-depth discussion of the original '60s TV scores and interviews with composers who worked on the series and films including Academy Award winning composers Jerry Goldsmith and Leonard Rosenman.